Organizational Learning from Extreme Performance Experience: The Impact of Success and Recovery Experience - Kim, June-Young; Kim, Ji-Yub (Jay); Miner, Anne S. (Organization Science, 2009)
This paper argues that two different types of a firm's own extreme performance experiences—success and recovery—and their interactions can generate survival-enhancing learning. Although these types of experience often represent valuable sources of useful learning, several important learning challenges arise when a firm has extremely limited prior experience of the same type. Thus, we theorize that a certain threshold of a given type of experience is required before each type of experience becomes valuable, with low levels of experience harming the organization. Furthermore, we propose that success and recovery experience will interact to enhance each other's value. These conditions can help overcome learning challenges such as superstitious learning or learning from small samples. We investigate our ideas using a sample of the U.S. commercial banks founded between 1984 and 1998. Our results indicate that both success and recovery experience of a firm generate survival-enhancing learning, but only after a certain level of experience is reached. Furthermore, success and recovery experience enhance each other's learning value, consistent with the theories that emphasize the importance of richer and contrasting experience in providing useful knowledge. Our framework advances organizational learning theory by presenting a contingent model of the impact of success and recovery experience and their interaction.